Edukasi dan Sayembara Peduli lingkungan "Teens Go Green" - Maria, Maria; Zega, Selly Artaty; Lumombo, Liony (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2024)
The "Teens Go Green" education and competition aimed to raise teens' awareness of eco issues and their impact on their daily lives. It is designed with contests and seminars to provide an in-depth understanding of eco issues. The competition provided a practical opportunity on how to be sustainable and eco-friendly which will be the content of the video. This service activity started with an Animation Video Competition in September, which was participated by high schools/vocational schools in Batam City. There are 35 students who have uploaded animated video works. The animated videos sent by the participants then went through a judging stage by the committee, to assess visual creativity and content in delivering environmental campaigns. The activity continued with the screening of all registered works. And continued to the "Teens Go Green" educational seminar as well as the announcement of the winner of the Animation Video Competition, which was held on October 20, 2023, at the Technopreneur Building, Batam State Polytechnic Campus. In the educational seminar session, the guest speaker was the 2016 Batam Environmental Ambassador and World Clean Up Day Activist of Batam, Deviana Wistiasari, S.M., M.M.. She raised the topic of environmental issues for millennials, gen Z and the role of the media in it. The event was attended by students and college students in Batam City, and even some from schools in Tanjung Pinang.